Correlates of Orthographic Learning in Swedish Children With Cochlear Implants - Wass, Malin; Löfkvist, Ulrika; Anmyr, Lena; Karltorp, Eva; Östlund, Elisabet; Lyxell, Björn (Frontiers in Psychology, 2019)
Deaf and hard of hearing children are at risk for reading difficulties due to poorer phonological skills which, in turn, are a consequence of their hearing impairment. With the introduction and development of cochlear implant intervention, the reading skills of these children have improved substantially although there is a high amount of variability within the group. Orthographic learning is the process of memorizing written words so that they can be recognized instantly and thereby allow for quick and fluent reading. This study set out to explore the cognitive and linguistic predictors of orthographic learning and reading fluency in a group of 40 deaf and hard of hearing children with cochlear implants, to better understand the factors that affect the development of fluent reading in these children. To date, the research about the mechanisms of reading fluency and orthographic learning in this population is scarce. The children were between 6;0 and 10;11 years of age and used oral language as their primary mode of communication. They were assessed on orthographic learning, reading fluency and a range of cognitive and linguistic skills including working memory measures, word retrieval and paired associate learning. The results were analyzed in a set of correlation analyses and hierarchical regression analyses. In line with previous findings from children with typical hearing, the strongest predictors of orthographic learning were phonological decoding fluency and verbal-verbal paired-associate learning. Phonological decoding fluency was the only significant predictor of word decoding fluency when age and non-verbal intelligence were controlled. The significant predictors of phonological decoding fluency were word retrieval, orthographic skills and visual working memory. The results of this study suggest that orthographic learning and reading fluency in children with CI are strongly dependent on similar cognitive and linguistic skills as in typically hearing peers. Efforts should thus be made to support phonological decoding skill and vocabulary in this population.